Physical Properties and Marshall Stability of High-Density Polyethylene and Rubber Crumb Modified Bitumen for Road Application - IGOMU, Sunday Ojoajogwu; BELLO, Tajudeen Kolawole; ISA, Muhammed Tijani (ABUAD Journal of Engineering and Applied Sciences, 2024)
Standard bitumen used in road construction may not meet engineering requirements due to it becoming brittle in cold weather and softening in hot weather. This study investigates the mechanical and physical properties of bitumen modified with high-density polyethylene (HDPE) and rubber crumb for road applications. Bitumen sourced from Ilaje, Ondo State, Nigeria, underwent characterisation tests including penetration, softening point, ductility, and fire point. Waste HDPE and rubber crumb, collected from dumpsites in Zaria, Kaduna State, Nigeria, were sorted, washed, dried, and milled to a size of 600 microns. The waste plastic was then blended with the bitumen using an optimised mix design obtained from the design of experiment. Characterisation tests (Marshall stability, penetration, softening point, ductility, and fire point) were performed on the resulting waste plastic-modified bitumen. The test results showed that the stability of the road asphalt increases as the proportion of HDPE and rubber crumb used in the bitumen modification increases. The control group (100% bitumen) exhibited the lowest Marshall stability (19.81 kN, 13.12 kN, and 17.82 kN for samples A, B, and C, respectively). The stability of sample A increased by 62.2%, the stability of sample B increased by 75.6%, and that of sample C increased by 56.6%. Based on the research findings, modifying bitumen with waste materials offers several advantages for road construction, which are reducing material costs as waste plastics and tires are readily available, waste utilisation reduces environmental impact, and modified bitumen enhances road durability.